2020
DOI: 10.1093/rfs/hhaa060
|View full text |Cite
|
Sign up to set email alerts
|

Do Neighborhoods Affect the Credit Market Decisions of Low-Income Borrowers? Evidence from the Moving to Opportunity Experiment

Abstract: Abstract This paper isolates the causal impact of neighborhood environment on the credit outcomes of low-income borrowers by analyzing the participants of the Moving to Opportunity (MTO) experiment. MTO was a unique, large-scale experiment that offered families vouchers to move to better neighborhoods via randomized lottery. We find higher credit scores and use among those required to move to the lowest poverty areas as young children. For those who moved as adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Finkelstein et al, 2012;Humphries et al, 2019), but lower than those generally reported in studies that included social security number as a match variable (e.g. Miller and Soo, 2018;.…”
Section: Data and Sample Constructionmentioning
confidence: 84%
“…Finkelstein et al, 2012;Humphries et al, 2019), but lower than those generally reported in studies that included social security number as a match variable (e.g. Miller and Soo, 2018;.…”
Section: Data and Sample Constructionmentioning
confidence: 84%
“…Finkelstein et al, 2012;Humphries et al, 2019), but lower than those generally reported in studies that included social security number as a match variable (e.g. Dobkin et al, 2018;Miller and Soo, 2018;Miller et al, 2021). 29 We are able to use survey data collected by the original Turnaway Study to better understand who was successfully matched to the credit database.…”
Section: Data and Sample Constructionmentioning
confidence: 95%
“…Reported match rates in each of these studies are 86%(Dobkin et al, 2018), 69%(Finkelstein et al, 2012), 61%(Humphries et al, 2019), 95%(Miller and Soo, 2018), and 99%(Miller et al, 2021).…”
mentioning
confidence: 99%
“…Prior ecological research finds supportive evidence for effects to emerge at the community level (79,(85)(86)(87). Higher concentrations of nuisance establishments like bars and alcohol outlets that often indicate economic marginalization and distress are associated with higher rates of child abuse and neglect, a relationship hypothesized to operate through communitylevel mechanisms (88)(89)(90)(91).…”
Section: Theoretical Mechanisms Linking Payday Lenders To Mortalitymentioning
confidence: 99%